The challenges in assessing children with complex needs for cochlear implantation: A case study. (September 2013) - Barker, Roz; Bathgate, Fionna
<x content-type="archive" xml:space="preserve">Abstract</x> This paper outlines some of the challenges in assessing children with complex needs for cochlear implantation. In addition, adaptations made to typical speech and language therapy and psychology assessment protocols are outlined.